Minimasi Human Error pada Operator Produksi Alat Kesehatan Menggunakan Pendekatan THERP-HAZOP - Dian Mardi Safitri; Ni Putu Githa Gayatri Prema Mahadevi; Sucipto Adisuwiryo (Jurnal Rekayasa Sistem Industri, 2023)
As production quantity increases to fulfill customer’s demand, the occupational accident occurs more compared to 2020. The need to use masks increased 20.15 times more in 2021 when the Delta variant of the COVID-19 virus entered Indonesia. This research observed the Manual Welding Machine labor in their process of producing head loop masks and aimed to design mitigation strategies for high error probability tasks. Methods used in this research are the Hierarchical Task Analysis (HTA) to define operator’s tasks, the Technique for Human Error Rate Prediction (THERP) to measure HEP, Event Tree Analysis to analyze the worst possibility of an incident, and the Hazard and Operability Study (HAZOP) to collect mitigation strategy. As the result of this research, several activities such as welding process preparation, picking up materials from the container, and materials preparation process have the highest HEP among all the activities. If some errors occur, it may cause light to severe injuries to the operators and the production area near the Manual Welding work station. Several mitigation plans are recommended to handle these problems, such as using warning displays and making SOP for operating Manual Welding Machine.